(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article examines the lithological and stratigraphic features of the geological structure of the Assakeaudan trough. Based on the drilling data, a structural map and a thickness map were compiled, and correlation schemes were analyzed to clarify the structure of the studied territory. Discovering productive horizons based on research results presents the greatest difficulties. In almost all fields of the Assakeaudian trough, opening and drilling in productive formations were carried out with a significant excess of bottomhole pressure over reservoir pressure. The possibility of absorption occurring and its intensity depend not only on the excess of the bottomhole pressure over the formation pressure, but also on the reservoir properties of the rocks, on what the reservoir is filled with.